2016
DOI: 10.1186/s40317-016-0104-9
|View full text |Cite
|
Sign up to set email alerts
|

Neckband or backpack? Differences in tag design and their effects on GPS/accelerometer tracking results in large waterbirds

Abstract: Background: GPS and accelerometer tracking presently revolutionises the fields of ecology and animal behaviour. However, the effects of tag characteristics like weight, attachment and data quality on study outcomes and animal welfare are important to consider. In this study, we compare how different tag attachment types influence the behaviour of a group of tagged large waterbirds, GPS accuracy and behaviour classification success from accelerometer data.Results: Both neckband and backpack tags had similar eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 69 publications
0
36
0
Order By: Relevance
“…In next spring (2013), six and four birds returned with working tags to fuel at the pasture and saltmarsh site, respectively, and no switches between the two habitat types were observed between years, nor within seasons (Fokkema et al., ). Because it may take some weeks for waterfowl to get accustomed to a tag (Kölzsch et al., ; Nuijten et al., ), we used this following spring for quantifying time budgets. Our birds frequently preened in the days after capture, but such behaviour was no longer observed next year.…”
Section: Methodsmentioning
confidence: 99%
“…In next spring (2013), six and four birds returned with working tags to fuel at the pasture and saltmarsh site, respectively, and no switches between the two habitat types were observed between years, nor within seasons (Fokkema et al., ). Because it may take some weeks for waterfowl to get accustomed to a tag (Kölzsch et al., ; Nuijten et al., ), we used this following spring for quantifying time budgets. Our birds frequently preened in the days after capture, but such behaviour was no longer observed next year.…”
Section: Methodsmentioning
confidence: 99%
“…In a captivity experiment, Kölzsch et al [44] reported no difference in behaviour between Canada Geese equipped with neck collar transmitters or backpack transmitters, but both groups tended to spend more time preening and less time feeding. Increased preening behaviour was also observed in a study on captive Bewick's Swans C. columbianus bewickii with neck collar transmitters, but this effect had disappeared after 6 weeks [57].…”
Section: Neck Collarsmentioning
confidence: 99%
“…Neck collars were used more often in the early 2000s, but have been used irregularly in the past 10 years. Apart from differences between attachment methods in adverse effects for waterfowl, the choice of attachment method should also depend on the research question of the researcher [44]. Harness-attached backpacks have the benefit of bringing the tracking device close the centre of gravity of the bird [44], while its placement on the back creates a large surface for charging of solar panels.…”
Section: Waterfowl Tracking: a Brief Historymentioning
confidence: 99%
See 2 more Smart Citations